2014
DOI: 10.1371/journal.pone.0097154
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Magnetosome Biomineralization - A Novel Platform to Study Molecular Mechanisms of Human CDF-Related Type-II Diabetes

Abstract: Cation diffusion facilitators (CDF) are part of a highly conserved protein family that maintains cellular divalent cation homeostasis in all organisms. CDFs were found to be involved in numerous human health conditions, such as Type-II diabetes and neurodegenerative diseases. In this work, we established the magnetite biomineralizing alphaproteobacterium Magnetospirillum gryphiswaldense as an effective model system to study CDF-related Type-II diabetes. Here, we introduced two ZnT-8 Type-II diabetes-related mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…S4A). Comparing the degree‐of‐openness values between the two MamB QH‐2 structures to those in other CTD‐CDF structures indicated that the two MamB QH‐2 CTDs showed closer similarity to the closed, metal‐bound structures of YiiP (∼30°) (Lu and Fu, ) than to the open, metal‐free structures of CzrB (∼53°) (Cherezov et al ., ) and MamM‐CTD (∼43°) (Zeytuni et al ., ) (Fig. B and C and Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 96%
“…S4A). Comparing the degree‐of‐openness values between the two MamB QH‐2 structures to those in other CTD‐CDF structures indicated that the two MamB QH‐2 CTDs showed closer similarity to the closed, metal‐bound structures of YiiP (∼30°) (Lu and Fu, ) than to the open, metal‐free structures of CzrB (∼53°) (Cherezov et al ., ) and MamM‐CTD (∼43°) (Zeytuni et al ., ) (Fig. B and C and Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, it has been suggested that bacterial CDFs may be capable of other activity such as mediating antibiotic resistance as is the case of CepA of Klebsiella pneumoniae that has been linked to chlorhexidine resistance [23], while two CDFs, MamB and MamM from Magnetospirillum gryphiswaldense were recently shown to be involved in magnetosome formation [101]. Interestingly, MamM has been used as a platform for studying CDF‐related type II diabetes because of the ease of measurement of its magnetism‐related phenotypes [114].…”
Section: Cdfs – More Than Heavy Metal Efflux Proteinsmentioning
confidence: 99%
“…Additionally, three MamM CTD metal binding sites were proposed that included two symmetrical, allosteric peripheral sites (PSs, composed of H264 from one monomer and E289 from the second monomer) and one central site (CS, composed of D249 and H285 from both monomers). Biophysical evidence revealed that zinc binding to the PSs leads to a change in protein conformation from an open, dynamic V-shaped dimer to a much tighter, rigid dimeric packing Barber-Zucker et al, 2019;Zeytuni et al, 2014bZeytuni et al, , 2014a.…”
Section: Introductionmentioning
confidence: 99%